2011
DOI: 10.1123/jpah.8.8.1160
|View full text |Cite
|
Sign up to set email alerts
|

Trails and Physical Activity: A Review

Abstract: There is a growing body of evidence demonstrating important factors that should be considered in promoting trail use, yet the evidence for positive effects of trails on physical activity is limited. Further research is needed to evaluate the effects of trails on physical activity. In addition, trail studies that include children and youth, older adults, and racial and ethnic minorities are a research priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 19 publications
(30 reference statements)
0
28
0
1
Order By: Relevance
“…This finding is not consistent with the majority of published studies that have indicated that physical activity declines with age. 8,30,31 In a national crosssectional study, Librett et al found that weekly and monthly trail use declined with age, with those ages 18-44 being 1.9-2.9 times more likely than adults ≥ 65 years to use trails at least once per month. 30 In the current study, we found that trail use may increase with age; however, our age categories are cruder, with those 40 to 64 years grouped with those 65 years and older.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is not consistent with the majority of published studies that have indicated that physical activity declines with age. 8,30,31 In a national crosssectional study, Librett et al found that weekly and monthly trail use declined with age, with those ages 18-44 being 1.9-2.9 times more likely than adults ≥ 65 years to use trails at least once per month. 30 In the current study, we found that trail use may increase with age; however, our age categories are cruder, with those 40 to 64 years grouped with those 65 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…8,26,27 Krizek et al found that living within walking distance of a trail increased use of the trail. 28 Other factors that were correlated with trail use include drinking water facilities and benches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A review of 52 studies of trails published between 1980 and 2008 only found one that included pre/post data with a comparison group (Starnes et al, 2011). That study (Brownson et al, 2004) examined the promotion of trails, not new trail construction, and did not find a significant change in overall walking activity.…”
Section: Introductionmentioning
confidence: 96%
“…36 Some researchers report mixed evidence for associations between the environment and physical activity. 72,116 Built community characteristics may have less of an impact on moderate or vigorous physical activity.…”
Section: Creation Of Healthier Habits and Environmental Influence On mentioning
confidence: 99%